Somalia : Technical Assistance Report-Internal Audit and Accounting Training for the Central Bank of Somalia. (IMF Staff Country Reports; Country Report ;, 2018)
This Technical Assistance Report discusses the recommendation made by the IMF mission to assist the authorities in Somalia in developing proper frameworks for internal auditing and accounting to bring them toward international accepted norms. The Internal Audit Department (IAD) needs an infrastructure to make the internal audit practices sustainable, repeatable, and professional. To this end, a proper internal audit charter, audit committee charter, and internal auditing manual needs to be drafted and approved by the management and Board of the Central Bank of Somalia (CBS). In addition, the management of the CBS should appoint a head for the IAD to lead the establishment of internal audit function and consider a flatter organizational structure so that the IAD can mobilize its resources more efficiently.